Pengembangan Media Pembelajaran Interaktif Berbasis Mobile Android pada Materi Karya Ilmiah Siswa Kelas XI - Anisa, Nofika; Rita, Rita; Amaluddin, Amaluddin (Jurnal Bahastra, 2025)
This study aims to analyze the development process, feasibility, and effectiveness of Android-based mobile interactive learning media designed to enhance students’ comprehension of scientific writing materials among grade XI students at SMA Negeri 16 Medan. Employing the 4-D development model by Thiagarajan—Define, Design, Develop, and Disseminate—the research involved a total population of 384 students, with a sample of 35 participants. The findings revealed that the developed product achieved a “highly feasible” category based on evaluations from media experts I and II, obtaining scores of 94% and 95%, respectively. Material experts I and II rated the media at 92% and 94%, while assessments from teachers I and II both yielded 94%. Field trials conducted with 35 students of class XI Draco at SMA Negeri 16 Medan showed a “highly feasible” rating of 88%. Furthermore, effectiveness testing through integrated evaluation instruments demonstrated significant improvement in students’ understanding of scientific writing materials, achieving a “highly effective” rating of 90%. These results indicate that the developed Android-based interactive media is both pedagogically sound and effective in supporting students’ learning outcomes.